2004
DOI: 10.1016/j.mod.2004.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish gcmb is required for pharyngeal cartilage formation

Abstract: The glial cells missing (gcm) gene in Drosophila encodes a GCM-motif transcription factor that functions as a binary switch to select between glial and neuronal cell fates. To understand the function of gcm in vertebrates, we isolated the zebrafish gcmb and analyzed the function of this gene using antisense morpholino oligonucleotides against gcmb mRNA (gcmb-MO) and transgenic overexpression. Zebrafish gcmb is expressed in the pharyngeal arch epithelium and in cells of the macrophage lineage. gcmb-MO-injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 67 publications
(89 reference statements)
3
32
0
Order By: Relevance
“…However, no consensus GCM-binding sites are present in the lz crystal cell-specific enhancer. Interestingly, it was recently shown that zebrafish gcmb is expressed in macrophages (Hanaoka et al, 2004). Yet, the putative functions of the two gcm homologues and their possible interplays with RUNX factors have not been investigated during vertebrate hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, no consensus GCM-binding sites are present in the lz crystal cell-specific enhancer. Interestingly, it was recently shown that zebrafish gcmb is expressed in macrophages (Hanaoka et al, 2004). Yet, the putative functions of the two gcm homologues and their possible interplays with RUNX factors have not been investigated during vertebrate hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent phylogenetic analysis of Gcm2 has led to a new theory that parathyroid glands in tetrapods are transformed from the gills of fish during evolution [11,26,27]. It has long been held that the parathyroid glands and PTH evolved with the emergence of the tetrapods, reflecting a need for new controls on calcium homeostasis in terrestrial, rather than aquatic, environments.…”
Section: Development and Evolution Of The Parathyriod Glandmentioning
confidence: 99%
“…Amphibians have parathyroid glands, whereas fish do not have these glands. Recent studies have indicated that the gill buds are homologous structures that play a similar role in controlling calcium levels [11,26,27]. Gcm2 is expressed in the pharyngeal arch epithelium starting in the 2nd pouch before extending to the other pouches, and later in the internal gill buds in both zebrafish and dogfish [11].…”
Section: Development and Evolution Of The Parathyriod Glandmentioning
confidence: 99%
“…In mice, FGF8 has been shown to induce Fgf3 expression in dental mesenchyme to regulate early tooth development (Åberg et al, 2004;Bei and Maas, 1998;Meyers et al, 1998). In zebrafish, Fgf3 expressed in the pharyngeal pouch endoderm regulates the formation of branchial arch cartilages, and depleting Fgf3 along with Fgf8 enhances the Fgf3-deficiency-induced cartilage defects whereas depleting Fgf8 expression alone causes an lesser effect on the jaw cartilage formation (David et al, 2002;Hanaoka et al, 2004;Herzog et al, 2004;Nissen et al, 2003;Walshe and Mason, 2003). These essential and conserved roles of Fgf signaling pathways in vertebrate craniofacial skeleton development are reflected directly by the clinical discoveries that several human cranial facial skeletal abnormalities, such as Beare-Stevenson syndrome, JacksonWeiss syndrome, Pfeiffer syndrome and otodental syndrome, are caused by defective FGF signaling (Gregory-Evans et al, 2007;Ornitz and Marie, 2002;Passos-Bueno et al, 1999;Walshe and Mason, 2003).…”
Section: Introductionmentioning
confidence: 99%